Correlates of toenail selenium and its cross‐sectional association with metabolic syndrome. Issue 5 (26th March 2018) - Jang, H.; Morris, J. S.; Park, K.
Abstract: Background: The present study aimed to identify independent correlates of toenail selenium levels and to examine the association between toenail selenium levels and metabolic syndrome in Korean adults. Methods: Cross‐sectional analysis was conducted using baseline data from the Trace Element Study of Korean Adults in the Yeungnam area, an ongoing cohort study of Korean adults over the age of 35 years. The baseline survey consisted of questionnaires on demographics, lifestyle characteristics and medical information. Dietary information was obtained through a validated semi‐quantitative food frequency questionnaire. Toenail selenium levels were quantified using neutron activation analysis. Biomarkers associated with metabolic syndrome were obtained from biennial medical check‐ups. Results: In the multivariable‐adjusted analyses, independent lifestyle and dietary correlates of higher selenium levels were alcohol drinking (4.62% higher than nondrinking) and egg intake (0.43% higher per weekly serving), whereas current smoking (5.42% lower than nonsmoking) and vegetable consumption (0.05% lower per weekly serving) were associated with lower toenail selenium levels. In the multivariable adjusted logistic regression, no significant association was observed between toenail selenium levels and metabolic syndrome (odds ratio = 1.33, 95% confidence interval = 0.58–3.05). Conclusions: Multiple lifestyle and dietary factors influenced toenail selenium levels, although no meaningful association was observed between toenail selenium levels and metabolic syndrome in Korean adults. Future prospective large‐scale cohort studies are required to determine whether there is a causal relationship between selenium levels and metabolic syndrome in Korean adults.